Pathogenicity of Rhizoctonia solani - Achmad; Hadi, Soetrisno; Herliyana, Elis Nina; Setiawan, Agus (Institut Pertanian Bogor (IPB University), 1999)
Pathogenicity of Rhizoctonia solani was studied by evaluating the ability of the pathogen to attack several ages of Pinus merkusii and Acacia mangium seedlings. Results showed that R. solani attacked P. merkusii from seed stage up to seven week-old seedlings, while eight week-old ones were free from the pathogen’s attack. On A. mangium, 16 day-old seedlings were uninfected by R. solani, while 12 day-old ones were still attacked by the pathogen. Pathogenesis of R. solani was also studied by evaluating the activities of cellulolytic and pectolytic enzymes produced by the fungi and compared them with the activities of the same enzymes produced by Fusarium oxysporum. Result showed that R. solani’s cellulolytic enzymes activity, reflected by the activity of C1-cellulase, was lower compared with that of F. oxysporum. On the other hand, R. solani was more intensive degrading pectin medium than F. oxysporum, such phenomenon reflected higher activity of pectolytic enzymes activity of R. solani compared with that of F. oxysporum.